A Qualitative Systematic Review of Exclusive Breastfeeding Practices in Indonesia: The Role of Family, Community Leaders, and Health Workers - Anila Iliani; Herawati Herawati; Hardyan Sauqi; Nelly Al Audhah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Exclusive breastfeeding (EBF) coverage in Indonesia remains far below the national target at only 20.7%. Understanding how family, community leaders, and health workers interact to influence mothers requires synthesizing qualitative evidence that captures lived experiences, power dynamics, and contextual meanings. This study aims to synthesize qualitative evidence on the roles and interactions of family, community leaders, and health workers in EBF decision-making in Indonesia. This qualitative systematic review was conducted following the PRISMA 2020 guidelines. A systematic search across Scopus, PubMed, and ProQuest for the period 2010-2025 identified 18 qualitative studies meeting the inclusion criteria. Data analysis employed thematic synthesis, which involved line-by-line coding of extracted findings, development of descriptive themes, and generation of analytical themes. These themes were then conceptually mapped based on Bronfenbrenner's socio-ecological theory to illustrate multi-level interactions. The close family (particularly parents/in-laws) played a dominant role as